Dampak Digitalisasi Ekonomi terhadap Pendapatan dan Laba UMKM Sasirangan di Kota Banjarmasin pada Masa Pandemi COVID-19 - Permatasari, Della Lorenza Putri (PPJP ULM, 2023)
This study has the following objectives: (1) to find out how the impact of the use of social media, marketplace, digital wallet, and Quick Response Code Indonesian Standard (QRIS) on the income and profits of Sasirangan SMEs in the city of Banjarmasin during the COVID-19 pandemic and (2) to find out how education, experience, and capital affect the income and profits of Sasirangan SMEs in the city of Banjarmasin during the COVID-19 pandemic. In this research, the writer uses the quantitative method through a descriptive approach. The type of primary data is obtained by distributing questionnaires and interviews. The analysis technique uses descriptive analysis and multiple linear regression using the Ordinary Least Square (OLS) method. The results of this study explain that economic digitization has a positive impact on increasing the income and profits of Sasirangan SMEs in the city of Banjarmasin. On the other hand, capital also affects the income and earnings of Sasirangan SMEs in Banjarmasin. All variables are statistically significant except for education and experience variables.